Clustering of functioning and disability profile based on the WHO disability assessment schedule 2.0 – a nationwide databank study. Issue 3 (30th January 2022) - Chen, Chao-Pen; Chen, Yi-Wen; Chang, Kwang-Hwa; Huang, Shih-Wei; Wu, Chien-Hua; Escorpizo, Reuben; Stucki, Gerold; Liou, Tsan-Hon
Abstract: Objective: To compare and cluster the health status and disability restrictions associated with eight major physiological functions of body systems, using functioning domains of WHO Disability Assessment Schedule 2.0. Design: Retrospective analyses of a nation-wide disability database. Setting: Population-based study. Participants: Records from patients >18 years of age with disability were obtained from the Taiwan Data Bank of Persons with Disability (July 2012–November 2017). Disability functioning profile of the following diagnosis were analyzed: stroke, schizophrenia, hearing loss, liver cirrhosis, chronic kidney disease, congestive heart failure, burn, head and neck cancer. Interventions: Not applicable. Main Outcome Measures: Demographic data, severity of impairment, and Disability Assessment Scale scores were obtained and analyzed. Radar charts were constructed using the WHO Disability Assessment Schedule 2.0. functioning domain score. Degree of similarity between any two given diagnosis was assessed by cluster analysis, comparing the Euclidean distances between radar chart data points among the six domains. Results: Based on cluster analysis of similarities between functioning domain profiles, the eight diagnoses were grouped into different disability clusters. Four clusters of disability were named according to the type restriction patterns: global-impact cluster (stroke); interaction-restriction cluster (schizophrenia, hearing loss); physical-limitation cluster, (liver cirrhosis, CKD, and congestive heart failure); and specific-impact cluster (burn, head and neck cancer). The rates of institutionalization and unemployment differed between the four clusters. Conclusion: We converted WHO Disability Assessment Schedule 2.0. functioning domain scores into six-dimensioned radar chart, and demonstrate disability restrictions can be further categorized into clusters according to similarity of functioning impairment. Understanding of disease-related disabilities provides an important basis for designing rehabilitation programs and policies on social welfare and health that reflect the daily-living needs of people according to diagnosis. Implication for Rehabilitation: The use of radar charts provided a direct visualization of the scope and severity of disabilities associated with specific diagnoses. Diagnosis-related disabilities can be organized into clusters based on similarities in WHODAS 2.0 disability domain profiles. Knowledge of the characteristics of disability clusters is important to understand disease-related disabilities and provide a basis for designing rehabilitation.